2021
DOI: 10.1093/alh/ajaa043
|View full text |Cite
|
Sign up to set email alerts
|

White Slave Fiction, So-Called

Abstract: In the early twentieth century, the widespread belief that young white women were at risk of being captured and forced into sex work led to significant legislative victories, and this crisis also shaped US literature in surprising ways. When writing about so-called white slavery crossed over from the spheres of journalism, social reform, and the law into fiction, authors devised a suite of quasi-empirical literary techniques that turned the dubious facts of white slavery into the stuff of popular art. Novelist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…She insisted that the real victims of the white slave trade were the gullible readers whose relentless consumption of white slavery narratives "drove them into an anxious frenzy." 16 Scholar Laura Fisher confirms, "Many Americans were already questioning the veracity of white slavery by the time Congress passed the Mann Act in 1910, and scholars now agree that no such crisis truly existed, at least not in the sensational form writers imagined." 17 However, like many of today's moral panics, there was, as Fisher suggests, a grain of truth underlying the growing obsession.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…She insisted that the real victims of the white slave trade were the gullible readers whose relentless consumption of white slavery narratives "drove them into an anxious frenzy." 16 Scholar Laura Fisher confirms, "Many Americans were already questioning the veracity of white slavery by the time Congress passed the Mann Act in 1910, and scholars now agree that no such crisis truly existed, at least not in the sensational form writers imagined." 17 However, like many of today's moral panics, there was, as Fisher suggests, a grain of truth underlying the growing obsession.…”
mentioning
confidence: 99%
“…16 Scholar Laura Fisher confirms, "Many Americans were already questioning the veracity of white slavery by the time Congress passed the Mann Act in 1910, and scholars now agree that no such crisis truly existed, at least not in the sensational form writers imagined." 17 However, like many of today's moral panics, there was, as Fisher suggests, a grain of truth underlying the growing obsession. 18 In 1982, historian Ruth Rosen compiled a number of interviews with sex workers conducted during the Progressive Era and found that 7.5 percent of the 6,309 women surveyed listed "white slavery" or "extreme coercion" as a causal factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation